Flower resource and land management drives hoverfly communities and bee abundance in seminatural and agricultural grasslands - Lucas, Andrew (Ecol Evol, 2017)
Pollination is a key ecosystem service, and appropriate management, particularly in agricultural systems, is essential to maintain a diversity of pollinator guilds. However, management recommendations frequently focus on maintaining plant communities, with the assumption that associated invertebrate populations will be sustained. We tested whether plant community, flower resources, and soil moisture would influence hoverfly (Syrphidae) abundance and species richness in floristically‐rich seminatural and floristically impoverished agricultural grassland communities in Wales (U.K.) and compared these to two Hymenoptera genera, Bombus, and Lasioglossum. Interactions between environmental variables were tested using generalized linear modeling, and hoverfly community composition examined using canonical correspondence analysis. There was no difference in hoverfly abundance, species richness, or bee abundance, between grassland types. There was a positive association between hoverfly abundance, species richness, and flower abundance in unimproved grasslands. However, this was not evident in agriculturally improved grassland, possibly reflecting intrinsically low flower resource in these habitats, or the presence of plant species with low or relatively inaccessible nectar resources. There was no association between soil moisture content and hoverfly abundance or species richness. Hoverfly community composition was influenced by agricultural improvement and the amount of flower resource. Hoverfly species with semiaquatic larvae were associated with both seminatural and agricultural wet grasslands, possibly because of localized larval habitat. Despite the absence of differences in hoverfly abundance and species richness, distinct hoverfly communities are associated with marshy grasslands, agriculturally improved marshy grasslands, and unimproved dry grasslands, but not with improved dry grasslands. Grassland plant community cannot be used as a proxy for pollinator community. Management of grasslands should aim to maximize the pollinator feeding resource, as well as maintain plant communities. Retaining waterlogged ground may enhance the number of hoverflies with semiaquatic larvae.